1995
DOI: 10.1046/j.1537-2995.1995.35695288769.x
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic versus therapeutic platelet transfusion practices in hematology and/or oncology patients

Abstract: The data from this study show that the majority of institutions use prophylactic platelet transfusion in both pediatric and adult hematology and/or oncology patients. However, there is considerable variation in platelet transfusion practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
1
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(60 citation statements)
references
References 12 publications
1
57
1
1
Order By: Relevance
“…14 In 1987, there were only a minority of 5% of leukemia and bone marrow transplant services which did not transfuse platelets prophylactially. 15 However, the hospitals using platelets prophylactically administered twice as many platelet transfusions.…”
Section: Discussionmentioning
confidence: 99%
“…14 In 1987, there were only a minority of 5% of leukemia and bone marrow transplant services which did not transfuse platelets prophylactially. 15 However, the hospitals using platelets prophylactically administered twice as many platelet transfusions.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that patients with acute leukemia and certain solid tumors can be managed relatively safely using prophylactic platelet transfusion thresholds lower than 20,000 cells/pl, or more complex prophylactic platelet transfusion policies that include the evaluation of clinical characteristics such as the presence of fever in addition to the platelet count [ 10-121. Nevertheless, even recently, prophylactic platelet transfusion for a platelet count less than 20,000 cells/pl was reported to be the most widely accepted policy in oncology practice in the United States [6].…”
Section: Management Of Thrombocytopenia and Associated Risks Plateletmentioning
confidence: 99%
“…In 1982, Murphy et al 42 published a prospective randomized trial comparing prophylactic and therapeutic transfusion policies in 56 pediatric leukemia patients treated from 1972 to 1976. The prophylactic threshold was set at 20,000 platelets/µL.…”
Section: Discussionmentioning
confidence: 99%